Fiction and pragmatics - Locher, Miriam A., 1972-; Jucker, Andreas H.; Landert, Daniela; Messerli, Thomas C. (Cambridge elements., 2023)
This volume outlines current issues in the study of the pragmatics of fiction. It starts from the premise that fictional texts are complex and multi-layered communicative acts which deserve attention in pragmatic research in their own right, and it highlights the need to understand them and to explore pragmatic effects and pragmatic theorising.